English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(z+i)^n+(z-i)^n=0
z member of C
n member of N

2006-10-22 19:58:53 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

Can you give the procedure and not just the result.

2006-10-22 20:11:28 · update #1

4 answers

devide by (z-i)^n

((z+i)/(z-i))^n + 1 =0

let (z+i)/(z-i) = t

t^n+ 1 = 0

this can be solved for n values of t

t^n = -1 = e^(pi*i) = e^(i*pi(2k+1)) for k from 0 to n- 1

this can be solved for t

then this can be solved for z

2006-10-22 20:13:01 · answer #1 · answered by Mein Hoon Na 7 · 0 0

Review your math book again and again until you understand better. Or go to your teacher for help.

2006-10-23 03:00:01 · answer #2 · answered by yahooaddict 4 · 0 1

z = cos u + isin u
then,
(z+i)^n = [(cos u + isin u) + i]^n = cos nu + isin nu + P(u) + i^n
(z-i)^n = [(cos u + isin u) - i]^n = cos nu + isin nu - P(u) - i^n

adding,
2cos nu + 2isin nu = 0
cos nu + isin nu = 0
(cos u + isin u)^n = 0
e^iu = 0

2006-10-23 04:45:46 · answer #3 · answered by yasiru89 6 · 0 0

It equals 2z^n

2006-10-23 03:03:16 · answer #4 · answered by Cycleogical 2 · 0 0

fedest.com, questions and answers